A new species of Acanthosaura Gray, 1831 (Reptilia: Agamidae) from the Truong Son Mountain Range, Vietnam - Hai Ngoc Ngo; Linh Tu Hoang Le; Tao Thien Nguyen; Tuan Minh Nguyen; Ngan Thi Nguyen; Tien Quang Phan; Truong Quang Nguyen; Thomas Ziegler; Dang Trong Do (European Journal of Taxonomy)
We describe a new species of the genus Acanthosaura Gray, 1831 from the Truong Son Mountain Range, southern Vietnam, based on integrative taxonomic analyses. Acanthosaura cuongi sp. nov. differs from its congeners by a combination of the following diagnostic characteristics: size moderate (snout-vent length: 79.4–104.61 mm); the absence of a diastema between the short nuchal and dorsal crest spines; vertebral crests composed of two rows of enlarged, keeled, pointed scales, arranged in a zipper line; various body coloration with light-green, orange-yellow, and light or purple-gray; black eye patch extending posteriorly to the anterior edge of tympanum. Maximum likelihood (ML) and Bayesian inference (BI) analyses using two mitochondrial genes (COI and Cytb) support the monophyly of Acanthosaura cuongi. Furthermore, the new species differs from the closest lineage consisting of A. coronata Günther, 1861 by having pairwise genetic distances of 11.58–12.11%, and have a maximal intraspecific distance of 0.35%. This is the 21st species of Acanthosaura and the tenth species of the genus reported from Vietnam.